Running Lean, Second Edition - Maurya, Ash (O'Reilly Media, Incorporated, 2019)
We live in an age of unparalleled opportunity for innovation. We're building more products than ever before, but most of them fail--not because we can't complete what we set out to build, but because we waste time, money, and effort building the wrong product. What we need is a systematic process for quickly vetting product ideas and raising our odds of success. That's the promise of Running Lean. In this inspiring book, Ash Maurya takes you through an exacting strategy for achieving a "product/market fit" for your fledgling venture, based on his own experience in building a wide array of products from high-tech to no-tech. Throughout, he builds on the ideas and concepts of several innovative methodologies, including the Lean Startup, Customer Development, and bootstrapping. Running Lean is an ideal tool for business managers, CEOs, small business owners, developers and programmers, and anyone who's interested in starting a business project. Find a problem worth solving, then define a solution Engage your customers throughout the development cycle Continually test your product with smaller, faster iterations Build a feature, measure customer response, and verify/refute the idea Know when to "pivot" by changing your plan's course Maximize your efforts for speed, learning, and focus Learn the ideal time to raise your "big round" of funding.
Keywords: Audiobooks